Nontuberculous Mycobacteria in Cystic Fibrosis - Furukawa, Brian S.; Flume, Patrick A. (Seminars in Respiratory and Critical Care Medicine, 2018)
Nontuberculous mycobacteria (NTM) can cause chronic pulmonary infection in susceptible hosts. Individuals with cystic fibrosis (CF), a multisystem disease predominated by progressive structural lung disease, are particularly vulnerable. Only recently have NTM been recognized for their potential to cause lung deterioration in CF patients. The reported prevalence varies widely from 4 to 40%, significantly more common than in the general population, but this varies because of multiple factors including inconsistent screening practices. Mycobacterium abscessus complex and Mycobacterium avium complex are the two most common species recovered. Defining NTM pulmonary disease in a CF patient can present challenges as it can be difficult to distinguish from the other potentially pathogenic organisms in the lung microbiome. In general, treatment regimens do not differ from the non-CF population but the clinician should be aware of potential interactions with other CF therapies. Recent population-level genomics has raised serious concern for indirect person-to-person transmission of several dominating NTM clones worldwide, raising awareness for increase prevention strategies when CF patients potentially congregate, such as clinic visits. Lung transplantation is controversial in those with NTM present in sputum culture but the available evidence suggests that this is not an absolute contraindication.
Keywords: nontuberculous mycobacteria; cystic fibrosis; MAC; Mycobacterium abscessus; bronchiectasis; cavitary lung disease